2006
DOI: 10.1111/j.1530-0277.2006.00023.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ethanol on Adenosine 5′‐Triphosphate–Gated Purinergic and 5‐Hydroxytryptamine3 Receptors

Abstract: This report of the proceedings of a symposium presented at the 2005 annual meeting of the Research Society on Alcoholism highlights the actions of ethanol on purinergic (P2XRs) and 5-hydroxytryptamine 3 (5-HT 3 Rs) receptors. Both P2XRs and 5-HT 3 Rs, are modulated by pharmacologically relevant concentrations of ethanol, with inhibition or stimulation of P2XR subtypes and stimulation of 5-HT 3 Rs, respectively. With regard to ethanol-modulatory actions, these 2 distinctly different receptor classes have been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…Compared with other ionotropic receptors gated by extracellular ligands, P2Xs constitute a relatively new family, yet their alcohol sensitivity (for review, see Weight et al, 1999; Dilger, 2002; Davies et al, 2006) has been explored since their initial pharmacological characterization. First reported in isolated bullfrog dorsal root ganglion neurons (Li et al, 1993), ethanol inhibition of native P2X receptors was also found in rat hippocampal CA1 neurons (Li et al, 2000) and in a slice preparation of rat ventral tegmental area that contains dopamine neurons and the GABAergic nerve endings impinging upon them, the P2X receptors being presumably located in the GABAergic presynaptic membrane (Xiao et al, 2008).…”
Section: Ethanol and Desensitization Of Extracellular Atp-gated Iomentioning
confidence: 99%
“…Compared with other ionotropic receptors gated by extracellular ligands, P2Xs constitute a relatively new family, yet their alcohol sensitivity (for review, see Weight et al, 1999; Dilger, 2002; Davies et al, 2006) has been explored since their initial pharmacological characterization. First reported in isolated bullfrog dorsal root ganglion neurons (Li et al, 1993), ethanol inhibition of native P2X receptors was also found in rat hippocampal CA1 neurons (Li et al, 2000) and in a slice preparation of rat ventral tegmental area that contains dopamine neurons and the GABAergic nerve endings impinging upon them, the P2X receptors being presumably located in the GABAergic presynaptic membrane (Xiao et al, 2008).…”
Section: Ethanol and Desensitization Of Extracellular Atp-gated Iomentioning
confidence: 99%
“…This interaction has important implications for the effect of ethanol on neurotransmission and the role of 5-HT3 receptors in alcoholism [54, 75-78], and along with preclinical and clinical results, has increased interest in the 5-HT3 receptor as a potential site for pharmacological treatment of alcohol and drug abuse [79, 80]. Ethanol also binds to, and potentiates the function of, other structurally related ligand gated ion channels, such as nACh receptors [78, 81].…”
Section: The 5-ht3 Receptormentioning
confidence: 99%
“…P2XRs are becoming a focus of investigation in ethanol studies because of building evidence suggesting that P2XRs are important mediators of ethanol-induced effects Davies et al, 2006;Asatryan et al, 2008;Tabakoff et al, 2009). ATP-gated currents are inhibited by ethanol at intoxicating and anesthetic concentrations when measured in P2X2Rs and P2X4Rs expressed in Xenopus oocytes Davies et al, 2002Davies et al, , 2005, whereas ATP-gated currents are potentiated by ethanol in P2X3Rs (Davies et al, 2005).…”
Section: Introductionmentioning
confidence: 99%